Energy consumption of a residential building: Comparison of conventional and RES-based systems - Michopoulos, Apostolos; Martinopoulos, Georgios; Papakostas, Konstantinos T.; Kyriakis, Nikolas A. (My University, 2009)
The energy needs of a typical one-family house in the Thessaloniki area for heating, cooling and domestic hot water production are calculated. The calculations are based on the typical average daily consumption of hot water and on the degree-day method for heating and cooling. The results are finally translated into thermal energy consumption, assuming the typical Greek situation (heating with diesel oil boilers and conventional radiators, cooling with local air-to-air split-type heat pumps and hot water production with electric heaters). The same energy needs are assumed to be covered by a vertical closed loop ground heat exchanger combined with a water-to-water heat pump system with fan-coils for heating and cooling and a thermosyphonic solar system for domestic hot water production. The ground heat exchanger/heat pump system efficiency is determined using data from an existing and continuously monitored similar system installed in the broader area of Thessaloniki. The solar system load coverage is calculated using the f-chart method. The energy consumption of the renewable energy systems is calculated and compared to that of the conventional system. The results prove that significant energy savings can be achieved.
Keywords: Heating/cooling energy consumption; RES-based heating/cooling system